PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK BERBANTUAN MEDIA QUESTION BOX UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 161 PEKANBARU - Vista, Nadila Aulia; Hermita, Neni; Zufriady, Zufriady (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2019)
The background of this study is caused by third-grade students’ low learning outcome in SDN 161 Pekanbaru. It is indicated by their social science test scores from 24 students. A minimum completeness criterion in this school is 75, but the number of students who score above this criterion is 8 students, and 16 students are below the criteria. The average score is 66.46. To solve this problem, the researchers apply a talking stick cooperative learning model assisted by question box media. This model is believed in supporting teachers in improving the learning activities because it can build a better classroom atmosphere that triggers students’ spirit and make students more active to express their opinions. Media use also makes students more interested in the learning process and stimulate students' emotional and intellectual involvement. This study applies the classroom action research that consists of two cycles. The subject is the third-grade students at SDN 161 Pekanbaru. After the implementation of the classroom action research, students’ learning outcomes increase from 66.46 to 75.83 in the first cycle (increase 14.10%), and 82.92 in the second cycle (increase 24.77% from the initial score). So, the implementation of the talking stick cooperative learning model assisted by question box media can increase third-grade students’ social science learning outcomes in SDN 161 Pekanbaru